Grammatical Cohesive Devices in “Beauty and the Beast” Short Story - Indah Sari (Budapest International Research and Critics University, 2022)
The aim of this the study was to analyze about grammatical cohesive devices in short story. This study was conducted by using descriptive qualitative and used document analysis. The source of the data was a short story entitled Beauty and the Beast. This study applied the Miles, Huberman and Saldana steps in analyzing the data. The results showed that there were types of grammatical cohesive devices in that short story namely reference, substitution and conjunction and reference was the most dominant type found in that short story.